2019
DOI: 10.3390/nu11040839
|View full text |Cite
|
Sign up to set email alerts
|

Poor Bifidobacterial Colonization Is Associated with Late Provision of Colostrum and Improved with Probiotic Supplementation in Low Birth Weight Infants

Abstract: This study aimed to evaluate the association between bifidobacterial colonization in low birth weight infants and perinatal factors, including the timing of initial colostrum and the effect of probiotics on this colonization. In this non-randomized controlled trial, we enrolled 98 low-birth-weight infants from a neonatal intensive care unit (NICU) in Japan. Infants were divided into three groups: group N (no intervention), group H (received non-live bifidobacteria), and group L (received live bifidobacteria). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Conventional bacterial culture methods confirm that the gut microbiota colonization of preterm infants is significantly different from that of healthy-term neonates. Compared with healthy-term infants, probiotics such as Bifidobacteria that regulate intestinal development in preterm infants, including epithelial barrier integrity, tend to colonize the intestinal tract of preterm infants late and less frequently, takes almost 1 week before colonization begins (Tanaka et al, 2019). In the investigation of preterm infant's fecal microbiota, we found that the colonization of intestinal Bifidobacteria in preterm infants was relatively late and did not rapidly develop into the dominant microbiota.…”
Section: Discussionmentioning
confidence: 82%
“…Conventional bacterial culture methods confirm that the gut microbiota colonization of preterm infants is significantly different from that of healthy-term neonates. Compared with healthy-term infants, probiotics such as Bifidobacteria that regulate intestinal development in preterm infants, including epithelial barrier integrity, tend to colonize the intestinal tract of preterm infants late and less frequently, takes almost 1 week before colonization begins (Tanaka et al, 2019). In the investigation of preterm infant's fecal microbiota, we found that the colonization of intestinal Bifidobacteria in preterm infants was relatively late and did not rapidly develop into the dominant microbiota.…”
Section: Discussionmentioning
confidence: 82%
“…Following Tanaka et al [38], real-time polymerase chain reaction (PCR) was performed using genus-specific primers capable of detecting Bifidobacterium spp., including GCL2505. The primer sequences were as follows: Bifidobacterium spp.…”
Section: Fecal Bifidobacteriamentioning
confidence: 99%
“…For the quantification of Bifidobacterium, a real-time polymerase chain reaction (PCR) was performed with Bifidobacterium genus-specific primers, as described previously [12,13]. B. bifidum OLB6378 was quantified using real-time PCR with strain-specific primers [14].…”
Section: Quantitative Analyses Of Bifidobacteriummentioning
confidence: 99%
“…B. bifidum OLB6378 was quantified using real-time PCR with strain-specific primers [14]. For the real-time PCR assay, bacterial genomic DNA was extracted from the stool samples using a commercial extraction kit (QuickGene DNA tissue kit, Kurabo, Osaka, Japan) as described previously [12,15]. The detection limits of Bifidobacterium and B. bifidum OLB6378 were 10 4 and 10 cells/g of faeces, respectively.…”
Section: Quantitative Analyses Of Bifidobacteriummentioning
confidence: 99%